Examining relationship between political agenda on social media and political support among university students - Ali Salman,; Mohd Azul Mohamad Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Social media have become the most readily available and important communication tools in the globalised world of today. As key sources of information, social media are responsible for delivering information and political news to the public making an impact on political support in Malaysia. Hence, the purpose of this study is to examine the role of social media in opening up space for political agenda and support among university students. A quantitative research approach using survey was used for data collection. A Questionnaire was used as an instrument to obtain data on the role of social media in political support among 200 respondents who were students of Universiti Kebangsaan Malaysia (UKM) and Universiti Putra Malaysia (UPM) in Klang Valley, Malaysia’s business hub. Using the Agenda Setting Theory, this study attempts to measure the relationship between political agenda on social media and political support. The findings show that political agenda on social media has a significant relationship with political support. Moreover, political agenda on social media plays a major role in political support. The results further show that social media provides information for understanding political issues in the country and at the same time empowers the people to share information about politics. This implies that social media provide a space for students to engage in political discussion leading to political support.